The relationship between prenatal attachment and death anxiety in high-risk pregnancies - Necla Kasımoğlu; Nazan G. Baş (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
This study aims to examine the relationship between prenatal attachment and death anxiety in high-risk pregnancies. The study, a descriptive and correlational design, was conducted with 158 women with high-risk pregnancies in eastern Türkiye between May and December 2024. Data were collected using a socio-demographic form, the Prenatal Attachment Inventory, and the Templer Death Anxiety Scale.The mean score on the Prenatal Attachment Inventory (PAI) was 62.1 ± 10.84, while the mean score on the Templer Death Anxiety Scale was 6.9 ± 2.99. A positive correlation was found between PAI and Death Anxiety scores (r = .169, p < .005). Death anxiety was predicted by maternal age and the level of prenatal attachment.